Hydrologic Assessment of Check Dam Performances in Semi-Arid Areas: A Case Study From Gujarat, India - Mozzi, Gloria; Pavelic, Paul; Alam, Mohammad F.; Stefan, Catalin; Villholth, Karen G. (Frontiers in Water, 2021)
In semi-arid India, managed aquifer recharge (MAR) is often used to enhance aquifer storage by capturing surface runoff, mainly through check dams implemented at the community level. Despite their extensive development, the design of these structures typically does not follow a systematic method to maximise performance. To aid in the process of improvement of check dams design parameters and location siting, we develop a tool which integrates daily water balance of check dam with analytical infiltration equations to asses check dam performance measured as temporal dynamics of storage, infiltration and evaporation. The tool is implemented in R environment and requires meteorological and hydrogeological data, as well as check dam geometry and nearby well abstractions, if any. The tool is applied to a case study in Saurashtra peninsula in Gujarat, where field visits were conducted. Simulations show that check dams annually are able to store between three and seven times their storage capacity. Infiltration volumes highly depend on hydroclimatic and hydrogeological conditions, as well as the formation of a clogging layer, highlighting the importance of site selection and periodic maintenance. Tool is validated with data from a previous study in Rajasthan, where daily water balance was monitored. Validation results show an average R2 of 0.93 between the simulated and measured water levels. The results are sufficiently promising to suggest that the tool developed in this study is able to evaluate check dam performance in different semi-arid regions.